The expansion of England two courses of lectures - Seeley, John Robert 1834-1895 (Cambridge library collection - British and Irish history, 19th century, 2011)
J. R. Seeley (1834–1895) was Regius Professor of Modern History at Cambridge. He was concerned that classics and the study of the distant past were far too dominant at the university, and believed that the academic study of contemporary history could provide a moral and intellectual foundation for modern political life. The Expansion of England, first published in 1883 and based on his lectures, was his most successful book, remaining in print for over seventy years. He believed that the purpose of the study of history was to see patterns and tendencies which could be used to make predictions about the future. Foreseeing the rise of America and Russia as world powers, he wanted to ensure that the British Empire retained its position of dominance in the twentieth century, which he saw as its destiny. His clear arguments, and skill in writing often-quoted epigrams, ensured the book's continued popularity